Homeless Veterans in Nursing Homes: Care for Complex Medical, Substance Use, and Social Needs. Issue 8 (17th June 2019) - Jutkowitz, Eric; Halladay, Christopher; McGeary, John; O'Toole, Thomas; Rudolph, James L.
Abstract : OBJECTIVES: The homeless population is aging, and their use of nursing homes is not well understood. We compared comorbidities (substance use, mental health conditions, and physical illness) and nursing home measures (source of admission, length of stay, and mortality in the facility) of veterans who were homeless, at risk for being homeless, or stably housed in the year prior to admission. DESIGN: Cross‐sectional analysis. SETTING AND PARTICIPANTS: All veterans admitted to a nursing home between January 2010 and December 2016 and their housing status in the year prior to their nursing home admission. MEASUREMENTS: Adjusted relative risks (ARRs) for the association between housing status, comorbidities, and nursing home measures. RESULTS: Veterans who were homeless in the year prior to their community nursing home admission were younger (n = 3355; 62.5 years [SD = 10.3 years]) at admission compared to stably housed veterans (n = 64 884; 75.3 years [SD = 11.9 years]). After adjustment for demographic characteristics, homeless veterans were more likely to have diagnoses for alcohol abuse (ARR = 2.18; 95% confidence interval [CI] = 2.05‐2.31), drug abuse (ARR = 3.03; 95% CI = 2.74‐3.33), mental health condition (ARR = 1.49; 95% CI = 1.45‐1.54), dementia (ARR = 1.14; 95% CI = 1.04‐1.25), liver disease (ARR = 1.32; 95% CI = 1.23‐1.41), lung disease (ARR = 1.08; 95% CI = 1.04‐1.13), and trimorbidity (co‐occurring substance abuse, mental illness, and physical illness) (ARR = 2.57; 95% CI = 2.40‐2.74) compared to stably housed veteran nursing home users. Homeless veterans were more likely to be admitted to a nursing home from a hospital (ARR = 1.13; 95% CI = 1.08‐1.17) and remain in the nursing home 90 days after admission (ARR = 1.10; 95% CI = 1.04‐1.16), but were less likely to die in the facility (ARR = 0.72; 95% CI = 0.67‐0.78) compared to stably housed veterans. CONCLUSIONS: Homeless veteran nursing home users have different characteristics than stably housed veteran nursing home users. These differences may challenge nursing home staff caring for homeless patients. Nursing homes should assess resident housing status to help provide linkages with existing social services. J Am Geriatr Soc 67:1707–1712, 2019